Alterações autonômicas e da sensibilidade somática em pacientes com doença de Crohn e retocolite ulcerativa - Coelho, Liana Santos de Melo (2012)
Many studies have demonstrated the involvement of the peripheral nervous system in inflammatory bowel disease (IBD). By quantitative sensation testing (QST) to search for the vibration and cold sensitive thresholds (evaluates thick and small fibres respectively) (protocol I) we assessed 29 patients with ulcerative colitis (UC), 30 patients with Crohn’s disease (CD) and 28 control patients. Questionnaires were applied to sensory complaints (protocol II) in 27 patients with CD, 24 patients with UC and 25 control patients. The same patients underwent stimulated skin wrinkling induced by water (SSW) (protocol III), which evaluates small fibre of the autonomic nervous system. The Fisher test and hypothesis test chi-square comparing the three groups (UC, CD and control) used in analysis of QST revealed more prone to peripheral neuropathy or sensory changes in patients suffering from UC and IBD (UC and CD) when evaluated respectively vibration and cold thermal sensitivity. Results of electromyography (EMG) was abnormal in 39,1% of UC and 38,4% CD patients. The questionnaire of sensory complaints (protocol II) showed prevalence of sensory complaints in 51,8% UC and 50% CD patients. There were several types of complaints, the most common, numbness in hands and feet. Three patients (two UC and one CD) presented with symptoms suggestive of “restless leg syndrome” and six patients had reported dizziness (autonomic dysfunction). Of the 14 UC and 12 CD patients with sensory complaints, 57,1% and 25% respectively had change in SSW. Of UC and CD patients who underwent SSW (protoco III), 48,1% and 41,7% had abnormal results, while the EMG was abnormal in 30% and 41,2 % respectively. We emphasize that TEC and QST seem better than EMG for diagnosis of sensory changes in patients with IBD, as many of these changes may correspond to small fibre neuropathy.